2008
DOI: 10.1002/cne.21744
|View full text |Cite
|
Sign up to set email alerts
|

Tauopathy with paired helical filaments in an aged chimpanzee

Abstract: An enigmatic feature of age-related neurodegenerative diseases is that they seldom, if ever, are fully manifested in nonhuman species under natural conditions. The neurodegenerative tauopathies are typified by the intracellular aggregation of hyperphosphorylated, microtubule-associated protein tau (MAPT) and the dysfunction and death of affected neurons. We document the first case of tauopathy with paired helical filaments in an aged chimpanzee (Pan troglodytes). Pathologic forms of tau in neuronal somata, neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
118
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 129 publications
(130 citation statements)
references
References 68 publications
(81 reference statements)
11
118
0
1
Order By: Relevance
“…These histopathological features are frequently observed in the aged brains of various nonhuman animal species. SPs and CAA have been observed in the brain of aged nonhuman primates [7,17,21,24], dogs [3,9,16,24,26], cats [18], a camel [19], bears [6,27], a wolverine [22], and a great spotted woodpecker [20], whereas NFTs have been reported only in a chimpanzee [23], sheep [5], bears [6], and a wolverine [22].…”
mentioning
confidence: 99%
“…These histopathological features are frequently observed in the aged brains of various nonhuman animal species. SPs and CAA have been observed in the brain of aged nonhuman primates [7,17,21,24], dogs [3,9,16,24,26], cats [18], a camel [19], bears [6,27], a wolverine [22], and a great spotted woodpecker [20], whereas NFTs have been reported only in a chimpanzee [23], sheep [5], bears [6], and a wolverine [22].…”
mentioning
confidence: 99%
“…27 It has been reported that some animals develop abnormally phosphorylated tau accumulation in neuronal cell bodies, and a recently reported chimpanzee was the first animal diagnosed with tauopathy. 43 As described above, only 2 individual Figure 6. Neuroanatomical distribution of Ab deposits and abnormally phosphorylated tau.…”
Section: Discussionmentioning
confidence: 88%
“…5 To our knowledge, the presence of Ab deposits and NFTs in the same individual has been detected in only 1 wolverine and 1 chimpanzee. 42,43 Since both of these were only case reports and intracranial infarction or hemorrhage was present in each and may have been the primary lesion responsible for NFTs, it remains unclear whether both findings of AD (NFTs and Ab deposits) spontaneously developed in these cases. Some researchers assume that AD is not present in animals because they do not live long enough to develop this slow-progressing disease.…”
mentioning
confidence: 99%
“…Primate species differences in neurodegeneration could be sought elsewhere in the APP gene, including the APP promoter (Maloney et al 2004). The tau peptide (MAPT gene) is also 100% identical in humans, chimpanzees, and in few other primates examined (Holzer et al 2004) as discussed in Rosen et al (2008).…”
Section: Species Differences In Relevant Genesmentioning
confidence: 95%